Hybrid solar, wind, and energy storage system for a sustainable campus : A simulation study - Muller, Dario Cyril; Selvanathan, Shanmuga Priya; Cuce, Erdem; Kumarasamy, Sudhakar (Editions Technip, 2023)
The reliance on grid electricity generated from fossil fuels in many countries continues to contribute to annual CO2 emissions. Implementing renewable energy systems helps reduce the carbon footprint and enhances local grid stability, particularly in areas with high demand where power outages are frequent. This study used the Hybrid Optimization of Multiple Energy Resources (HOMER) software to determine the most cost-effective composition of a Hybrid Renewable Energy System (HRES). Simulation results indicate that a system comprising a 3007 PV array, two 1.5 MW wind turbines, and a 1927 kW converter is most suitable. Combining solar panels and wind turbines remains the most economically feasible option for on-site electricity production. The study demonstrates that installing a hybrid renewable energy system is viable on an academic campus, with an initial investment cost of US $6.58 million and yearly operational costs of US $1.38 million, which is 40.8% lower than the current system. The project payback time is estimated to be 10.11 years. These findings may be used to recommend similar systems in other regions with comparable climatic conditions. The positive monetary effects may incentivize policymakers to implement comparable systems, contributing to a carbon-neutral goal.